A non-linear three-dimensional model for quantifying microbubble dynamics - Patil, Abhay V. (Acoustical Society of America, 2010)
A three-dimensional non-linear model for simulating microbubble response to acoustic insonation is presented. A 1 μm radius microbubble stimulated using positive and inverted 2.4 MHz pulses produced radius-time curves that matched (error <10%) with the experimental observation. A bound 2.3 μm radius microbubble insonated using 2.25 MHz 6 cycle pulse was observed to oscillate with max∕min oscillations 45% lower than that of the free microbubble, this correlated (∼10% error) with the observations of Garbin et al. [Appl. Phys. Lett. 90, 114103 (2007)]. The adherent microbubble oscillated asymmetrically in the plan view and symmetrically in the elevation view, consistent with the previous experimental results.